Exposure of the heart and cardiac valves in women irradiated for breast cancer 1970–2009. (September 2022) - Duane, Frances K.; Boekel, Naomi B.; Jacobse, Judy N.; Wang, Zhe; Aleman, Berthe M.P.; Darby, Sarah C.; Schaapveld, Michael; van Leeuwen, Flora E.; Baaijens, Margreet H.A.; Warren, Samantha; Taylor, Carolyn W.
Highlights: Cardiac exposure decreased substantially 1970–2009. Direct megavoltage IMC beams likely increase the risks of IHD and VHD. Cardiac dosimetry from past regimens is highly heterogeneous. Dosimetry from past decades is key for dose–response relationships for late effects. A wide variation in valve doses may enable a dose–response relationship for VHD. Abstract: Purpose: To describe cardiac exposure from breast cancer radiotherapy regimens used during 1970–2009 for the development of dose–response relationships and to consider the associated radiation-risks using existing dose–response relationships. Material and methods: Radiotherapy charts for 771 women in the Netherlands selected for case control studies of heart disease after breast cancer radiotherapy were used to reconstruct 44 regimens on a typical CT-dataset. Doses were estimated for the whole heart (WH), left ventricle (LV) and cardiac valves. Results: For breast/chest wall radiotherapy average WH doses decreased during 1970–2009. For internal mammary chain (IMC) radiotherapy WH doses were highest during the 1980s and 1990s when direct anterior fields were used and reduced in the 2000s when oblique fields were introduced. Average doses varied substantially for IMC regimens (WH 2–33 Gy, LV < 1–23 Gy). For cardiac valves, at least one valve received >30 Gy from most regimens. Conclusions: Radiation-risks of IHD from breast/chest wall regimens likely reduced during 1970–2009. Direct anterior IMC regimens likely increased the risks of IHD and VHD over this time period but the use of oblique IMC fields from 2003 may have lowered these risks. These data provide a unique opportunity to develop dose–response relationships.